Optimization of grade-separated road and railway crossings based on a distance transform algorithm. Issue 2 (1st February 2022) - Pu, Hao; Liang, Zhu; Schonfeld, Paul; Li, Wei; Wang, Jianxi; Zhang, Hong; Song, Taoran; Wang, Jie; Hu, Jianping; Peng, Xianbao
Abstract : The design of grade-separated road and railway crossings can be complicated and time-consuming since the intersection point as well as the road and rail alignments should jointly optimize an objective such as minimum construction costs. Moreover, the design of grade-separated road and railway crossings should consider additional crossing constraints and possible revisions of the road alignments. However, research on alignment optimization with variable ends is scarce. In this article, a grade-separated road and railway crossing model is developed, the crossing point of which as well as both connection points with the road, are variable. Subsequently, by searching synchronously for the paths that connect different endpoints, a distance transform algorithm is applied. The effectiveness of the method is verified through a real-world case study. The results show that the proposed method can find various promising solutions that both satisfy multiple constraints and are considerable improvements on the designs produced by experienced human designers.